Persepsi Kesiapan Mahasiswa Akuntansi dalam Menghadapi Tantangan di Era Revolusi Industri 4.0 - Pradnyani, Ni Luh Putu Norma Dewi Abdi; Pramitari, I Gusti Ayu Astri; Abdi, I Nyoman (E-Jurnal Akuntansi, 2021)
This research examines the influence of accounting understanding, soft skills, information technology knowledge on the readiness of accountants in facing the challenges of the industrial revolution era 4.0. This study uses primary data in the form of questionnaires that contain statements related to research, data collection using purposive sampling techniques that are sampling with certain criteria. The sample in this study is the final semester students majoring in accounting of Bali State Polytechnic. The number of samples in this study was 137 samples. The questionnaire deployment data is statistically analyzed using the SPSS program with multiple linear regression methods, classical assumption tests, T and F tests, and coefficients of determination. The test results showed a significant positive influence between accounting understanding, soft skills, and information technology knowledge on readiness to face the challenges of the industrial revolution era 4.0. Keywords: Accounting Understanding; Soft skills; IT Comprehension; Industry 4.0.